Bheshajakaala and its Clinical Importance–A Review on the Physiological Basis - Resmi, B G; Chhaju, Yadav Ram; Abhilash, M (International Research Journal of Ayurveda & Yoga, 2022)
The concept of time of administration of drugs (Bheshajakaala) is an important area in Ayurveda to be focused on. Even though the different types and indications of the different bheshajakaala are mentioned in classics how far they are executed in management of diseases by proper analysis is to be thought of. For the proper execution of these principles, there should be clarity and proper understanding of the concepts. The Ayurveda classics have given the details regarding drug administration viz. types, description of each type, conditions in which they are to be applied etc. but there is no direct reference regarding the exact reason for choosing these particular time period in particular condition. Here, an attempt is made to explain the logic of indicating each bheshajakaala in different conditions for the better understanding of the concept. The descriptions integrating modern physiological principles could prove pivotal in explaining the rationale for bheshajakaala and thereby facilitating their judicious use in clinical practice.